Efficient screening of brinjal genotypes for bacterial wilt resistance at seedling stage: Unravelling the mechanisms through biochemical parameters - Niharika Muslepally; Namboodiri, Raji Vasudevan (Journal of Tropical Agriculture, 2024)
Brinjal genotypes were screened for resistance to bacterial wilt (BW) caused by Ralstonia solanacearum at the seedling stage and biochemical parameters were analysed to uncover the underlying resistance mechanisms. Three-week-old seedlings of 31 brinjal genotypes including four resistant checks(RC: Ponny, Haritha, Surya and Neelima) and two susceptible checks [SC:SM-26,(S.incanum),SM-27(S.insanum)] were subjected to a screening procedure that combined soil drenching and root dip inoculation.Based on percentage disease incidence (PDI), two accessions SM-15 and SM-25 were rated as highly resistant(HR: 0 PDI) and accession SM-1 was rated as resistant(R: 1-10PDI). Accessions SM-1, SM-2, SM-5, SM-11, SM-17,SM-24 and KAU hybrid Neelima were rated as moderately resistant (MR: 11-20 PDI). Accessions SM-4, SM-8, SM-14 and SM-19 were rated as susceptible (S: 21-30 PDI). Moderately susceptible (MS: 31-40 PDI) accessions were SM-3, SM-32, SM-33, SM-13 and SM-16. Accessions SM-9, SM-10, SM-12, SM-18, SM- 20, SM-21, SM-22, SM-23, SM-26 and SM-27 were rated as highly susceptible (HS:>40PDI). Biochemical analysis showed higher phenol content, Polyphenol Oxidase (PPO) activity, and total sugars in resistant and moderately resistant groups at 12 and 24 hours post inoculation (hpi). PPO activity, phenolic and total sugars had a strong negative correlation with disease incidence at 12 and 24 hpi.